Zika Virus Inhibitors Based on a 1,3-Disubstituted 1H-Pyrazolo[3,4-d]pyrimidine-amine Scaffold - Eunkyung Jung; Ruben Soto-Acosta; Robert J. Geraghty; Liqiang Chen (Molecules, 2022)
To search for Zika virus (ZIKV) antivirals, we have further explored previously reported 7H-pyrrolo[2,3-d]pyrimidines by examining an alternative substitution pattern of their central scaffold, leading to compound 5 with low micromolar antiviral activity. To circumvent the synthetic difficulties associated with compound 5, we have exploited a 1H-pyrazolo[3,4-d]pyrimidine scaffold and performed structure-activity relationship studies on its peripheral rings A and B. While ring B is less sensitive to structural modifications, an electron-withdrawing group at the para position of ring A is preferred for enhanced antiviral activity. Overall, we have not only discovered an alternative substitution pattern centered on a 1H-pyrazolo[3,4-d]pyrimidine scaffold but also generated anti-ZIKV compounds including 6 and 13, which possess low micromolar antiviral activity and relatively low cytotoxicity. These compounds represent new chemotypes that will be further optimized in our continued efforts to discover anti-ZIKV agents.